Formação continuada de professores do ensino fundamental I: subsídios para uma proposta em análise - Mantovanini, Regiane (2009)
The title of this dissertation: Teacher Continuing Education in Ensino Fundamental I : subsides for a proposition in analysis arose from some questions along the researcher s life, school and professional experience. Along her continuing education, the author noticed the changes in her view and in her theoretical and practical knowledge. She noticed how that knowledge enriched her work. However, the formative investments were not enough for all teachers. By having to handle work overload (forty eight to sixty hours a week), the teachers had very little possibility to attend continuing education programs out of their working hours. The continuing education in service sometimes was the only formative opportunity for most teachers; that is the reason why the author started to question the usual teacher continuing education programs and their subsides for practice. Thus, the problem for the present research arose. How the experienced models analyzed here may or may not help teachers take a new pedagogical model, by offering clues to a continuing education that makes sense for the group of teachers as well as for practice transformation? The present work brings the hypothesis that a continuing education that makes sense to the teachers could provoke changes in educational and social context. In search for the answer to that question, the methodology approach involves qualitative, bibliographical and documental research regarding exploratory, descriptive, analytical, evaluative and interpretative research, focusing some principles and actions of propositions for continuing education that are developed in the researched school, trying to understand how those practices may or may not help teachers take a new pedagogical model. The data collection is made from observation and description of situations in school documents. The data analysis is based on theoretical referred authors. The referred school is a city public school in São Bernardo do Campo/SP. The researcher works in that school as PAP (Pedagogical Coordinator). The involved subjects are teachers under her coordination in formative activities and other school management workers: principal, assistant principal, Educational program teacher, Interactive school library teacher and Pedagogical Counselor. The dissertation conclusion is that it is possible to develop continuing education of good quality. It shows the difficulties to find a systematized and intentional work as well as the factors that favor or complicate the formative process of the group of teachers in their work site. It shows didactic propositions, evaluation and their repercussion in the teacher s pedagogical and practical scenario